Intervenção educativa em hanseníase para médicos residentes de áreas clínicas - Silva, Karem Christine Corrêa e (2020)
Hansen’s Disease (HD) is often neglected and is a concern for public health, being of notice that Brazil is second worldwide in new diagnosed cases. It is a contagious condition and although curable may leave sequels that worsen its stigma. Currently, at the moment of diagnosis, the degree of physical incapability has been high, which demonstrates late suspicion. It is of extreme importance the realization of research that bring alert to the institutions of medical education about the need of improving its professional qualification. Our goal has been to verify the degree of knowledge of medical residents of clinical areas in PUC-SP in assisting patients with HD. This is a quantitative, descriptive and transversal study made with 19 medical residents in clinical areas of PUC-SP Medicine School in 2019. The data was collected through 2 self-applied questionnaires (the first with sociodemographic profile and 4 closed questions, and the second answered before and after the educational intervention). The sample consisted mainly of women (84%), younger than 30 years (63%) and graduated in the last 5 years (79%). The increase in immediate knowledge on average corresponded to 17.5% and was significant by the Student’s t test. The difficulties found in some closed questions (to about 80% of participants) were related to diagnosis and treatment, being confirmed by the answers of the pre/post test where there were larger increases of right answers (above 30%, with p<0.05). These findings may be related to an excessively theoretical formation, without practical training. Therefore, we conclude that there is a need to incentive future contextualized activities that ground the knowledge of medical residents about this condition